MOTIVASI KERJA APARATUR SIPIL NEGARA DI KANTOR KECAMATAN SERAWAI KABUPATEN SINTANG - Hahury, Jhony Fredy (Universitas Kapuas Sintang, 2024)
: the inquire about points to decide and portray the work inspiration and commitment of state respectful workers in carrying out government assignments. Collection methods incorporate : in-depth interviews, perception, and documentation thinks about. The investigate witnesses comprised of the sub-district head, the sub-district secretary, and two state respectful hirelings from the Serawai sub-district office. The investigate comes about appear that inspiration has to be actualized and inspiration can be expanded and kept up by increasing in value the performance of the device within the shape of grants given within the shape of laud, motivations and advancements. Everything is done to energize work excitement in arrange to move forward the proficient and dependable execution of the device. Separated from giving inspiration, the organization gives consideration to the device through a commitment to advance positions and stipends to the device who work genuinely and ended up propelled to move forward their execution. Commitments are made so that representatives appear dependability in carrying out their obligations and capacities to the most extreme.